2019
DOI: 10.4103/1673-5374.251330
|View full text |Cite
|
Sign up to set email alerts
|

Early treadmill exercise increases macrophage migration inhibitory factor expression after cerebral ischemia/reperfusion

Abstract: The neuroprotective function of macrophage migration inhibitory factor (MIF) in ischemic stroke was rarely evaluated. This study aimed to investigate the effects of early treadmill exercise on recovery from ischemic stroke and to determine whether these effects are associated with the expression levels of MIF and brain-derived neurotrophic factor (BDNF) in the ischemic area. A total of 40 male Sprague-Dawley rats were randomly assigned to the ischemia and exercise group [middle cerebral artery occlusion (MCAO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This signaling mainly suppresses c-Jun N-terminal kinase activation, leading to inhibited apoptosis [ 13 , 17 ]. In addition, MIF exerts neuroprotective effects by inducing BDNF [ 22 , 23 , 26 ], which may be mediated via the CD74–ERK1/2 pathway [ 26 ]. Specifically, a pre-pro form of BDNF protein is first synthesized followed by subsequent removal of the pro-region [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This signaling mainly suppresses c-Jun N-terminal kinase activation, leading to inhibited apoptosis [ 13 , 17 ]. In addition, MIF exerts neuroprotective effects by inducing BDNF [ 22 , 23 , 26 ], which may be mediated via the CD74–ERK1/2 pathway [ 26 ]. Specifically, a pre-pro form of BDNF protein is first synthesized followed by subsequent removal of the pro-region [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have reported that MIF mainly plays a neuroprotective role in ischemic stroke [ 22 , 23 ]. In these studies, we found that MIF was neuroprotective in ischemic stroke models via the inhibition of neuronal cell apoptosis and induction of brain-derived neurotrophic factor (BDNF) expression.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests a potential therapeutic role of MIF in the treatment of MI (Cui et al, 2016). Additionally, MIF expression can also be induced by exercise, and it has been identified as an exercise-induced cardioprotective factor that protects against MI (Chang et al, 2019).…”
Section: Other Exercise-induced Polypeptidesmentioning
confidence: 79%
“…Clinically, early exercise has been proven to be an effective method to promote motor recovery in patients with ischemic stroke (1,2). Experimental studies have also demonstrated that treadmill training is beneficial in ameliorating neurological deficits in rats after cerebral ischemia (3,4). Further analysis of the mechanism of exercise-induced neuroprotection revealed decreased activation of resident cells such as microglia and astrocytes (5,6), suppressed expression of pro-inflammatory cytokines (6,7), and reduced leukocyte infiltration in the penumbra (8,9), results consistent with our previous findings (10).…”
Section: Introductionmentioning
confidence: 99%